A Randomized Trial of Lorcaserin and Lifestyle Counseling for Maintaining Weight Loss Achieved with a Low‐Calorie Diet. Issue 2 (29th December 2017) - Shaw Tronieri, Jena; Wadden, Thomas A.; Berkowitz, Robert I.; Chao, Ariana M.; Pearl, Rebecca L.; Alamuddin, Naji; Leonard, Sharon M.; Carvajal, Ray; Bakizada, Zayna M.; Pinkasavage, Emilie; Gruber, Kathryn A.; Walsh, Olivia A.; et al.
Abstract : Objective: Improving the maintenance of lost weight remains a critical challenge, which can be addressed by long‐term behavioral and/or pharmacological interventions. Methods: This study investigated the efficacy of combined behavioral and pharmacological treatment in facilitating weight loss maintenance (WLM) in 137 adults (86.1% female; 68.6% black; BMI = 37.0 ± 5.6 kg/m 2 ) who had lost ≥ 5% of initial weight during a 14‐week low‐calorie diet (LCD) program (mean = 9.3 ± 2.9%). Participants were randomly assigned to lorcaserin (10 mg twice a day) or placebo and were provided 16 group WLM counseling sessions over 52 weeks. Results: At 24 weeks post randomization, more lorcaserin‐treated than placebo‐treated participants maintained a ≥ 5% loss (73.9% vs. 57.4%; P = 0.033), and the lorcaserin‐treated participants lost an additional 2.4 ± 0.8 kg versus a 0.6 ± 0.8 kg gain for placebo ( P = 0.010). However, at week 52, groups did not differ on either co‐primary outcome; 55.1% and 42.6%, respectively, maintained ≥ 5% loss ( P = 0.110), with gains from randomization of 2.0 ± 0.8 kg and 2.5 ± 0.8 kg ( P = 0.630), respectively. From the start of the LCD, groups maintained reductions of 7.8% and 6.6%, respectively ( P = 0.318). Conclusions: Combined behavioral and pharmacological treatment produced clinically meaningful long‐term weight loss in this group of predominantly black participants. Lorcaserin initially improved upon weight loss achieved with WLM counseling, but this advantage was not maintained at 1 year.